Development and Validation of a Virtual Examination Tool for Firearm Forensics1, 2, 3. Issue 4 (16th October 2017) - Duez, Pierre; Weller, Todd; Brubaker, Marcus; Hockensmith, Richard E.; Lilien, Ryan
Abstract: The transition from 2D imaging to 3D scanning in the discipline of firearms and toolmark analysis is likely to provide examiners an unprecedented view of microscopic surface topography. The digital examination of measured 3D surface topographies has been referred to as virtual microscopy (VM). The approach offers several potential advantages over traditional comparison microscopy. Like any new analytic method, VM must be validated prior to its use in a crime laboratory. This paper describes one of the first validation studies of virtual microscopy. Fifty‐six participants at fifteen laboratories used virtual microscopic tools to complete two proficiency‐style tests for cartridge case identification. All participating trained examiners correctly reported 100% of the identifications (known matches) while reporting no false positives. The VM tools also allowed examiners to annotate compared surfaces. These annotations provide insight into the types of marked utilized in comparative analysis. Overall, the results of the study demonstrate that trained examiners can successfully use virtual microscopy to conduct firearms toolmark examination and support the use of the technology in the crime laboratory.